C‐terminal neurogranin is increased in cerebrospinal fluid but unchanged in plasma in Alzheimer's disease. Issue 12 (16th June 2015) - De Vos, Ann; Jacobs, Dirk; Struyfs, Hanne; Fransen, Erik; Andersson, Kerstin; Portelius, Erik; Andreasson, Ulf; De Surgeloose, Didier; Hernalsteen, Daniëlle; Sleegers, Kristel; Robberecht, Caroline; Van Broeckhoven, Christine; et al.
Abstract: Introduction: Biomarkers monitoring synaptic degeneration/loss would be valuable for Alzheimer's disease (AD) diagnosis. Postsynaptic protein neurogranin may be a promising cerebrospinal fluid (CSF) biomarker but has not yet been evaluated as a plasma biomarker. Methods: Using an in‐house designed prototype enzyme‐linked immunosorbent assay (ELISA) targeting neurogranin C‐terminally, we studied neurogranin in paired CSF/plasma samples of controls (n = 29) versus patients experiencing MCI, or dementia, due to AD (in total n = 59). Results: CSF neurogranin was increased in AD and positively correlated with CSF tau, whereas there was a negative relationship between CSF neurogranin (and tau) and CSF Aβ1–42 /Aβ1–40 . No differences were detected in plasma neurogranin between controls and AD. Also, there was no correlation between CSF and plasma neurogranin, excluding confounding effects of the latter. Discussion: This study strengthens the potential of neurogranin as an AD CSF biomarker, which now needs validation in larger studies. As tools, straightforward immunoassays can be used, as demonstrated by the described ELISA.